(untitled) (Herald of the National Children’s Medical Center, 2025)
In children with sepsis, timely restoration of tissue perfusion is vital to prevent multiple organ failure and fatal outcomes. Standard hemodynamic indicators such as blood pressure (BP) and heart rate (HR) do not always reflect the true status of tissue blood flow. Therefore, it is necessary to use additional markers that are available for clinical monitoring, including lactate levels, urine output, capillary refill time, and venous oxygen saturation.